(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This short essay highlights how the COVID-19 crisis forced many faculty members in the higher education setting to abruptly transition from face-to-face and hybrid instruction to remote teaching. We highlight how emergency remote teaching can lead to overall improved instruction (regardless of future course modality) and better preparedness (for future crises) through an asserted effort to reflect on the experience as a whole.